2022
DOI: 10.3390/en16010417
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Modeling of Magnetic Materials under 3D Vectorial Magnetization for Electrical Machine Design and Analysis

Abstract: The magnetic properties of magnetic cores are essential for the design of electrical machines, and consequently appropriate mathematical modeling is needed. Usually, the design and analysis of electrical machines consider only the one-dimensional (1D) magnetic properties of core materials, i.e., the relationship of magnetic flux density (B) versus magnetic field strength (H), and their associated power loss under 1D magnetization, in which the B and H are constrained in the same orientation. Some studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Therefore, it is essential to investigate the magnetic properties of nanocrystalline and amorphous magnetic materials under 2-D magnetizations, although only a few studies have been reported so far [ 81 , 89 , 90 , 91 ]. Furthermore, some electrical machines may have three-dimensional (3-D) rotating magnetic fields, and the magnetic properties of the core materials under 3-D magnetizations must also be explored [ 82 , 83 , 84 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is essential to investigate the magnetic properties of nanocrystalline and amorphous magnetic materials under 2-D magnetizations, although only a few studies have been reported so far [ 81 , 89 , 90 , 91 ]. Furthermore, some electrical machines may have three-dimensional (3-D) rotating magnetic fields, and the magnetic properties of the core materials under 3-D magnetizations must also be explored [ 82 , 83 , 84 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…With the utilization of the 3D magnetic testing system, extensive experimental results have been acquired by subjecting various material samples to different magnetization patterns, including 1D alternating flux, 2D circularly rotating flux, and 3D spherical flux densities. More details concerning the experimental results can be found in our previous publications [15,84]. With the utilization of the 3D magnetic testing system, extensive experimental results have been acquired by subjecting various material samples to different magnetization patterns, including 1D alternating flux, 2D circularly rotating flux, and 3D spherical flux densities.…”
Section: Magnetic Properties and Their Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…To tackle these challenges, numerous research endeavors have been undertaken. These include the application of novel and advanced electromagnetic materials exhibiting lower specific power loss and improved high-frequency characteristics , advanced modeling of material properties that account for the actual operational conditions of electric motors [38][39][40][41][42], the implementation of application-oriented, system-level, multi-disciplinary, multi-objective robust design and optimization considering various factors, manufacturing uncertainties, and operational conditions [43][44][45][46][47][48], as well as the development of advanced control methods to optimize operational performance [49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Other works ( [18][19][20][21]) have treated the same problem; however, the apparatuses used are similar to the ones previously referred to. An apparatus capable of 3D excitation and measurement was treated in [22], consisting of 3D coil systems for both the excitation and the measurement. Due to its design, the apparatus does not allow the application of mechanical stress.…”
Section: Introductionmentioning
confidence: 99%